The Influence of Viral Marketing and Fear of Missing Out (FOMO) on Impulsive Buying of Miniso x Harry Potter Products in Surabaya - Ella Elvina Yuwono; Zumrotul Fitriyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study was to determine the effect of viral marketing and fear of missing out, or FOMO, on impulsive buying at Miniso X Harry Potter in Surabaya. This study uses quantitative methods with data collection techniques through distributing questionnaires to a population of Miniso X Harry Potter consumers in Surabaya. The sampling method is non-probability sampling with a purposive sampling technique, so that the total number of samples taken is 90 respondents. Performing data analysis with SmartPLS software. Based on the research results, it is known that viral marketing and fear of missing out or FOMO contribute to the impulsive buying of Miniso X Harry Potter collaboration products in Surabaya.